Analysing CO2 emissions from transportation expenditures by Malaysian households - Abdullah Chik, Norlaila; Hassan, Kalthum; Ayob, Wahida (2017)
This study analyses the impact of Malaysian household consumption on the transportation sector regarding CO2 emissions by using the Hybrid Input Output Table from 1991, 2000, 2005 and 2010. Initially, this study calculates CO2 emissions intensity for every sector.Results show that the sector with the highest CO2 emission intensity was Transportation at 1.16 (T- CO2/M-MyR).By using the hybrid, I-O table, the average values of the total CO2 emission intensity caused by energy consumption in Malaysia were found to be 0.272 (T- CO2/M-MyR).Transportation sector contributed the relatively high level of consumption and produces the highest amount of CO2 emission in 1991, 2000, 2005 and 2010.Our analysis shows that continuously increasing consumption in the Transportation sector will continue to affect the environment. Thus, through encourage consumers to use hybrid or solar cars and the imposition of a carbon tax on old vehicles, owners will reduce their CO2 emissions.By imposing a carbon tax, motor vehicle owners will strive to reduce their CO2 emissions by consuming renewable energy or use energy saving techniques in their everyday lifestyle.